Preparation method and application of xenon lamp exposure aging resistant black halogen-free flame retardant nylon

Ethyl oleate, bis(acetylacetone)diisopropyltitanate and tea are used by adding polyamide resin, glass fiber, halogen-free flame retardant compound and water-oxygen barrier modifier to the nylon material. The synergistic effect of polyphenols has prepared black halogen-free flame-retardant nylon with anti-xenon lamp exposure, which solves the problems of aging and insufficient flame-retardant performance of nylon materials under xenon lamp exposure, and achieves higher mechanical properties and environmental protection.

CN119286242AActive Publication Date: 2025-01-10GUANGDONG GREAT MATERIAL CO LTD

Patent Information

Application Number
CN202411576503.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-01-10
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

Nylon materials age severely under xenon lamp exposure, have large color changes, mechanical properties deteriorate, and their flame retardant properties are insufficient. Especially under the limitations of environmental protection requirements, traditional flame retardants have problems with smoke and toxic gas emissions.

Method used

Using a preparation method, including polyamide resin, glass fiber, halogen-free flame retardant compound and water-oxygen barrier modifier, the anti-xenon lamp exposed to aging black halogen-free resistance is prepared by high-speed mixing and twin-screw extrusion granulation process. Nylon-burning, water oxygen barrier modifier is prepared by reaction of ethyl oleate, bis(acetylacetone)diisopropyltitanate and tea polyphenols, enhancing the water oxygen barrier and anti-aging properties of the material.

Benefits of technology

It significantly improves the anti-aging and flame retardant properties of nylon materials under xenon lamp exposure, reduces color changes and mechanical performance reduction, and meets the safety and environmental protection requirements of automotive accessories.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005121930330000061
    Figure BDA0005121930330000061
Patent Text Reader

Abstract

The invention provides a preparation method and application of xenon lamp exposure aging resistant black halogen-free flame retardant nylon. The xenon lamp exposure aging resistant black halogen-free flame retardant nylon is prepared from the following raw materials in percentage by weight: 30-50% of polyamide resin, 10-30% of glass fiber, 10-30% of a halogen-free flame retardant compound, 1-3% of an antioxidant, 5-15% of a water-oxygen barrier modifier and 1-3% of black masterbatch. The xenon lamp exposure aging resistant black halogen-free flame retardant nylon prepared by the preparation method of the xenon lamp exposure aging resistant black halogen-free flame retardant nylon can adapt to long-term outdoor use requirements, has excellent xenon lamp exposure aging resistant and flame retardant properties, and is widely applied to automobile parts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of nylon materials, and in particular to a preparation method and application of black halogen-free flame-retardant nylon resistant to xenon lamp exposure and aging. Background Art

[0002] With the continuous advancement of science and technology, polymer materials are increasingly used in various fields. As an important engineering plastic, nylon has excellent mechanical properties, heat resistance, wear resistance and chemical corrosion resistance, and is widely used in electronics, automobiles, aerospace and other fields.

[0003] During use, nylon materials will be affected by various environmental factors, such as light, temperature, humidity, oxygen, etc., which will cause the performance of the material to gradually decline and aging. Among them, light is one of the main factors that cause nylon material aging. As a light source that simulates sunlight, xenon lamps have the characteristics of high intensity and high energy, which can accelerate the aging process of nylon materials. The aging of nylon materials under xenon lamp exposure is mainly manifested in color changes, mechanical property degradation, surface cracks, etc. After aging, not only the appearance quality of nylon materials will decline, but also its mechanical properties and service life will be greatly reduced, which will affect its application in various fields.

[0004] Nylon material is a flammable material. During the combustion process, a large amount of smoke and toxic gases will be produced, which poses a serious threat to people's lives and property. Plastic parts used in new energy vehicle accessories need to have good flame retardant properties to improve the safety of new energy vehicles. In order to improve the flame retardant properties of nylon materials, people usually use the method of adding flame retardants. Traditional flame retardants mainly include halogen flame retardants and phosphorus flame retardants. Although halogen flame retardants have good flame retardant effects, they will produce a large amount of smoke and toxic gases during the combustion process, causing serious harm to the environment and human health. Although phosphorus flame retardants are relatively environmentally friendly, they also have some problems, such as low flame retardant efficiency and poor compatibility with nylon materials. In order to solve the flame retardant problem of nylon materials and meet environmental protection requirements at the same time, people have conducted a lot of research on halogen-free flame retardant reinforced nylon. At present, halogen-free flame retardant reinforced nylon mainly uses the addition of halogen-free combustion aids, nanocomposites, reactive flame retardants and other methods to improve the flame retardant properties of nylon.

[0005] The current halogen-free flame-retardant reinforced nylon materials have some problems in terms of resistance to xenon lamp exposure and aging, such as poor aging resistance and large color changes. Therefore, the SAE-2527 standard specifies the aging test methods and performance requirements for automotive materials under xenon lamp exposure, providing a reference for the selection and design of automotive materials, and providing reference value for the study of halogen-free flame-retardant reinforced nylon that resists xenon lamp exposure and aging.

[0006] In view of the problems existing in the prior art, the present application aims to solve the problems of poor flame retardancy of nylon materials, severe aging under xenon lamp exposure, large color changes, and decreased mechanical properties. Summary of the invention

[0007] Purpose of the invention: The purpose of the present invention is to provide a method for preparing black halogen-free flame-retardant nylon resistant to xenon lamp exposure and aging, so that the prepared black halogen-free flame-retardant nylon resistant to xenon lamp exposure and aging can solve the problems of poor flame retardancy of nylon materials, severe aging under xenon lamp exposure, large color changes, and decreased mechanical properties.

[0008] The technical solution of the present invention:

[0009] The invention discloses a method for preparing xenon lamp exposure resistant black halogen-free flame-retardant nylon, characterized in that the raw materials for preparing the xenon lamp exposure resistant black halogen-free flame-retardant nylon include the following components based on 100% by weight: 30-50% polyamide resin, 10-30% glass fiber, 10-30% halogen-free flame retardant compound, 1-3% antioxidant, 5-15% water-oxygen barrier modifier, and 1-3% black masterbatch.

[0010] Furthermore, the weight average molecular weight of the polyamide resin is 18 to 25 kDa.

[0011] Furthermore, the halogen-free flame retardant compound is prepared by mixing nano silicon dioxide, zinc borate, magnesium hydroxide and ammonium polyphosphate; the mass ratio of the nano silicon dioxide, zinc borate, magnesium hydroxide and ammonium polyphosphate is 10-20:1:2-5:8-20.

[0012] Furthermore, the water and oxygen barrier modifier is prepared by reacting ethyl oleate, bis(acetylacetonato) diisopropyl titanate, and tea polyphenols.

[0013] The preparation of the water-oxygen barrier modifier comprises the following steps:

[0014] S1: Add an appropriate amount of toluene into a reaction vessel equipped with a stirrer, a thermometer, and a reflux condenser, and heat to a certain temperature;

[0015] S2: adding ethyl oleate to the reaction vessel in step S1, stirring to fully dissolve it, and then slowly dropping bis(acetylacetonato)diisopropyl titanate, stirring is maintained during the dropping process, and after the dropping is completed, reacting at a certain temperature for a period of time;

[0016] S3: After the reaction is completed, tea polyphenols are slowly added to the reaction vessel in step S2 in batches, and the temperature is increased to react for a period of time;

[0017] S4: After the reaction is completed, the reaction product is cooled to room temperature, and then filtered, distilled, and purified to obtain a water-oxygen barrier modifier.

[0018] Furthermore, the mass ratio of ethyl oleate, bis(acetylacetonato)diisopropyl titanate and tea polyphenols is 5-10:0.5-2:1.

[0019] The present application provides a method for preparing a xenon lamp resistant black halogen-free flame-retardant nylon, characterized in that it comprises the following steps:

[0020] Step 1: Add polyamide resin, halogen-free flame retardant compound, antioxidant, water-oxygen barrier modifier and black masterbatch into a high-speed mixer for premixing, the speed of the high-speed mixer is 500-1000 rpm, and the mixing time is 5-10 minutes;

[0021] Step 2: soaking the glass fiber in a silane coupling agent solution with a mass concentration of 1 to 3% for 10 to 30 minutes, taking out the glass fiber after soaking, drying it and setting it aside;

[0022] Step 3: Add the premixed material in step 1 and the soaked glass fiber in step 2 into a twin-screw extruder for extrusion granulation, the extrusion temperature is 200-260° C., and the screw speed is 100-300 rpm;

[0023] Step 4: After the material is extruded, it is cooled and vacuum dried to obtain black halogen-free flame-retardant nylon that is resistant to xenon lamp exposure and aging.

[0024] Furthermore, the heating temperature of step S1 is 80-100° C.; the stirring speed of step S2 is 100-300 rpm, the reaction temperature is 80-100° C., and the reaction time is 2-4 hours; the reaction temperature of step S3 is 100-120° C., and the reaction time is 4-6 hours.

[0025] Furthermore, the antioxidant is one or more of antioxidant 1098, antioxidant 1010, antioxidant 1216, and antioxidant 1330.

[0026] The present application also provides a method for preparing black halogen-free flame-retardant nylon resistant to xenon lamp exposure and aging, and the application of the prepared black halogen-free flame-retardant nylon resistant to xenon lamp exposure and aging in automobile supporting plastic parts or automobile engine peripheral parts.

[0027] The water-oxygen barrier modifier formed by the reaction of ethyl oleate, diisopropyl bis(acetylacetonate) titanate and tea polyphenols has good water-oxygen barrier and anti-aging effects in nylon materials through their respective effects and mutual synergy. The role of ethyl oleate: providing hydrophobic properties. Ethyl oleate belongs to fatty acid esters and has hydrophobicity. In nylon materials, it can form a hydrophobic layer on the surface and inside of the material to prevent the penetration and absorption of water. Water is one of the important factors leading to material aging. Reducing the entry of water can improve the water resistance and stability of the material, thereby indirectly improving the anti-aging properties of the material; auxiliary dispersion effect. Ethyl oleate can be used as an auxiliary dispersant to help other ingredients disperse better in the nylon matrix. For example, it can make halogen-free flame retardant compounds, antioxidants, etc. dispersed more evenly in nylon to ensure the uniformity of material performance. At the same time, for the added glass fiber, ethyl oleate can also play a certain lubricating and dispersing role, reduce the agglomeration between glass fibers, and improve the mechanical properties of the material. The role of bis(acetylacetonate) diisopropyl titanate: Enhance interfacial bonding. Bis(acetylacetonate) diisopropyl titanate is a titanate coupling agent. It can react with the active groups on the nylon molecular chain to form chemical bonds or strong physical adsorption between nylon and other additives (such as glass fiber, halogen-free flame retardant, etc.), thereby enhancing interfacial bonding. Good interfacial bonding can effectively transfer stress, improve the mechanical properties of the material, and reduce the defects and pores inside the material, reduce the permeation channels of water and oxygen, and play a role in water and oxygen barrier; improve processing performance. The titanate coupling agent can also improve the processing performance of nylon materials. It can reduce the melt viscosity of the material, make the material easier to flow and shape during processing, and reduce energy consumption and equipment wear during processing. At the same time, good processing performance also helps the material maintain uniformity during processing and improve the quality and performance stability of the product. The role of tea polyphenols: Antioxidant effect. Tea polyphenols are a natural antioxidant with strong antioxidant capacity. In nylon materials, tea polyphenols can capture free radicals and prevent them from attacking nylon molecular chains, thereby slowing down the oxidative aging process of the material. Free radicals are one of the important factors that lead to material aging. By removing free radicals, tea polyphenols can effectively improve the anti-aging properties of the material; Synergistic effect: Tea polyphenols and antioxidants have a synergistic effect. Antioxidants mainly play the role of inhibiting oxidation reactions in materials, and the addition of tea polyphenols can further enhance the effect of antioxidants and improve the antioxidant properties of materials. At the same time, there may also be interactions between tea polyphenols and ethyl oleate and bis(acetylacetonato) diisopropyl titanate, which can jointly improve the water-oxygen barrier properties and anti-aging properties of the material. Beneficial effects:

[0028] The invention provides a method for preparing black halogen-free flame-retardant nylon resistant to xenon lamp exposure and aging, so that the prepared black halogen-free flame-retardant nylon resistant to xenon lamp exposure and aging solves the problems of serious aging, large color change, mechanical property degradation and surface cracks of automobile nylon parts under xenon lamp exposure for a long time in outdoor use. DETAILED DESCRIPTION

[0029] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.

[0030] Polyamide resin (PA66, weight average molecular weight of 20 kDa) was purchased from Shanghai Fuchen Plastic Raw Materials Co., Ltd.; ammonium polyphosphate was purchased from Wuhan Jiyesheng Chemical Co., Ltd.; and glass fiber was purchased from Jushi Group Co., Ltd.

[0031] Unless otherwise specified, the chemical reagents used in the present invention are all commercially available analytically pure.

[0032] Preparation of halogen-free flame retardant compounds:

[0033] S1: Add 20 kg of nano-silicon dioxide into 20 L of ethanol and use an ultrasonic dispersion device for ultrasonic treatment for 30 minutes at an ultrasonic power of 200 W to obtain a nano-silicon dioxide dispersion;

[0034] S2: Add 1 kg of zinc borate, 2 kg of magnesium hydroxide and 8 kg of ammonium polyphosphate into a high-speed mixer, set the speed of the high-speed mixer to 800 rpm, and mix for 15 minutes;

[0035] S3: slowly add the nano-silicon dioxide dispersion prepared in step S1 into the high-speed mixer prepared in step S2 and continue mixing for 20 minutes; S4: take out the halogen-free flame retardant compound prepared in step S3 from the high-speed mixer, dry it, and sieve it through a 100-mesh sieve to obtain the halogen-free flame retardant compound.

[0036] Preparation of water and oxygen barrier modifier A:

[0037] S1: Add 500 mL of toluene into a reaction vessel equipped with a stirrer, a thermometer, and a reflux condenser, and heat to 80°C;

[0038] S2: Add 5 g of ethyl oleate to the reaction vessel of step S1, stir to fully dissolve it, then slowly drop 1 g of bis(acetylacetonato)diisopropyl titanate, keep stirring during the dropwise addition, the stirring speed is 200 rpm, after the dropwise addition is completed, the reaction temperature is 80°C, and the reaction is carried out for 2 hours;

[0039] S3: After the reaction is completed, 1 g of tea polyphenols is slowly added in batches to the reaction vessel of step S2, and the reaction temperature is raised to 100° C. The reaction time is 4 hours.

[0040] S4: After the reaction is completed, the reaction product is cooled to room temperature, and then filtered, distilled, and purified to obtain a water-oxygen barrier modifier.

[0041] Preparation of water and oxygen barrier modifier B:

[0042] The difference between this preparation and the water-oxygen barrier modifier A is that 5g of ethyl oleate and 1g of bis(acetylacetonato)diisopropyl titanate in step S2 are replaced with 10g of ethyl oleate and 1g of bis(acetylacetonato)diisopropyl titanate. Preparation of water-oxygen barrier modifier C:

[0043] The difference between this preparation and the water-oxygen barrier modifier A is that 5g of ethyl oleate and 1g of bis(acetylacetonato)diisopropyl titanate in step S2 are replaced with 3g of ethyl oleate and 3g of bis(acetylacetonato)diisopropyl titanate. Preparation of water-oxygen barrier modifier D:

[0044] The difference between this preparation and the water-oxygen barrier modifier A is that 5g of ethyl oleate and 1g of bis(acetylacetonato)diisopropyl titanate in step S2 are replaced with 12g of ethyl oleate and 0.5g of bis(acetylacetonato)diisopropyl titanate. Preparation of water-oxygen barrier modifier E:

[0045] The difference between this preparation and the water-oxygen barrier modifier A is that 1 g of tea polyphenols in step S3 is replaced by 5 g of tea polyphenols.

[0046] Preparation of black halogen-free flame-retardant nylon resistant to xenon lamp exposure and aging:

[0047] Step 1: Add polyamide resin, halogen-free flame retardant compound, antioxidant, water-oxygen barrier modifier and black masterbatch into a high-speed mixer for premixing. The speed of the high-speed mixer is 800 rpm and the mixing time is 10 minutes.

[0048] Step 2: Soak the glass fiber in a 1% mass concentration of vinyl triethoxysilane-ethanol solution for 10 minutes. After soaking, take out the glass fiber, dry it in the air, and set it aside;

[0049] Step 3: Add the premixed material in step 1 and the soaked glass fiber in step 2 into a twin-screw extruder for extrusion granulation at an extrusion temperature of 260° C. and a screw speed of 250 rpm;

[0050] Step 4: After the material is extruded, it is cooled by water cooling and vacuum dried to obtain black halogen-free flame-retardant nylon that is resistant to xenon lamp exposure and aging.

[0051] Examples 1 to 6

[0052] According to the above-mentioned preparation method of xenon lamp exposure resistant black halogen-free flame retardant nylon, Table 1 is the ingredient list of xenon lamp exposure resistant black halogen-free flame retardant nylon of Examples 1 to 6 in percentage.

[0053] Table 1

[0054]

[0055] Comparative Example 1:

[0056] Comparative Example 1 was prepared according to the above-mentioned method for preparing black halogen-free flame-retardant nylon resistant to xenon lamp exposure and aging. The difference between this preparation and Example 2 is that no halogen-free flame retardant compound was added.

[0057] Comparative Example 2:

[0058] Comparative Example 2 was prepared according to the above-mentioned method for preparing black halogen-free flame-retardant nylon resistant to xenon lamp exposure and aging. The difference between this preparation and Example 2 is that: the water and oxygen barrier modifier A is not added.

[0059] Comparative Example 3:

[0060] The difference between the present preparation and Example 2 is that in the preparation of the black halogen-free flame-retardant nylon resistant to xenon lamp exposure and aging, glass fiber is directly used in step 2 without soaking the glass fiber.

[0061] Performance test: The nylon materials prepared in Examples 1 to 6 and Comparative Examples 1 to 3 were subjected to xenon lamp exposure aging resistance, flame retardancy, and Shore hardness tests. The specific test methods are as follows:

[0062] 1. Xenon lamp exposure aging resistance: According to the standard SAE J2527, the nylon materials prepared in Examples 1 to 6 and Comparative Examples 1 to 3 are prepared into 2×5×10 cm long strip samples. Before the xenon lamp exposure aging test, the samples need to be cleaned, dried and other pre-treated to remove surface pollutants and moisture to ensure the accuracy of the test results. The prepared samples are installed on the sample rack in the test box to ensure that the samples can be evenly exposed to the xenon lamp and the environmental conditions in the test box. The lamp irradiance level reaches 0.55 watts / square meter·nanometer. During the light cycle, the air temperature in the test box is maintained at 47°C; during the dark cycle, the air temperature is 38°C; the relative humidity during the light cycle is 50%, and the relative humidity during the dark cycle is increased to 95%; during the light cycle, the black panel temperature needs to reach 70°C. Before the test, it is necessary to set 18 hours of light, 6 hours of dark environment, and 10 cycles of light and dark cycles, and the sample surface needs to be sprayed with water during the light and dark environments; the test results are evaluated using a 3000MW 2 ... The Ci7800 colorimeter from Source Instrument Equipment Co., Ltd. quantitatively measures the color change of the sample after 10 cycles of light and dark cycles. When the color difference ΔE is less than 1, the human eye can hardly observe the color change; when ΔE is between 1 and 2, only professionally trained people or under specific conditions can perceive the slight change in color; when ΔE is between 2 and 3, the human eye can clearly perceive the color change; when ΔE is between 3 and 5, the color change is more significant; when ΔE is greater than 5, the color change is very large and is generally considered unacceptable; the Shore hardness of the sample after 10 cycles of light and dark cycles was tested with the OU2700 hardness tester from Cangzhou Oupu Testing Instrument Co., Ltd.

[0063] 2. Flame retardancy test: The nylon materials prepared in Examples 1 to 6 and Comparative Examples 1 to 3 are prepared into strips with a size of 125 mm × 13 mm × 3 mm, and the strips are fixed vertically on the fixture of the combustion box to ensure that the lower end of the strip is 5 cm away from the top of the burner. According to the standard requirements, the flame height and temperature of the burner are adjusted. The blue inner flame height is 20 mm, the outer flame height is 40 mm, and the temperature is 550 ° C. A combustion test is carried out, and the lower end of the strip is ignited to observe the combustion behavior of the strip. Record the burning time and burning length of the strip. Evaluation level: According to the burning time and burning length, the flame retardant properties of the strip are evaluated according to the standard. It is divided into V-0, V-1, and V-2 levels. V-0 level indicates the best flame retardant performance, V-1 level indicates average flame retardant performance, and V-2 level indicates the worst flame retardant performance.

[0064] Table 2: Test results

[0065] Material Color difference ΔE hardness Flame retardant grade Example 1 1.2 D85 V-0 Example 2 1.1 D88 V-0 Example 3 1.2 D85 V-0 Example 4 1.8 D75 V-1 Example 5 2.0 D77 V-1 Example 6 2.1 D72 V-1 Comparative Example 1 2.5 D80 V-2 Comparative Example 2 3.0 D64 V-2 Comparative Example 3 1.8 D76 V-2

[0066] From the above data, it can be seen that the xenon lamp exposure aging resistant black halogen-free flame-retardant nylon of Examples 1 to 3 has excellent xenon lamp exposure aging resistance and flame retardant properties; from the comparison between Example 4 and Example 2, it can be seen that the mass ratio of ethyl oleate and bis(acetylacetonate) diisopropyl titanate in the preparation of the water and oxygen barrier modifier is unreasonable, which will cause the color difference of the xenon lamp exposure aging resistance of the prepared black halogen-free flame-retardant nylon to become larger, the hardness and the flame retardant properties to become worse; from the comparison between Example 5 and Example 2, it can be seen that when preparing the water and oxygen barrier modifier, too much ethyl oleate will cause the color difference of the xenon lamp exposure aging resistance of the prepared black halogen-free flame-retardant nylon to become larger, the hardness and the flame retardant properties to become worse; from the comparison between Example 6 and Example 2, it can be seen that when preparing the water and oxygen barrier modifier, the amount of tea polyphenols is increased, ethyl oleate, bis(acetylacetonate) If the mass ratio of diisopropyl titanate and tea polyphenols is unreasonable, the color difference of the xenon lamp resistant black halogen-free flame retardant nylon after xenon lamp exposure and aging will be larger, and the hardness and flame retardant properties will be worse; from the comparison between comparative example 1 and embodiment 2, it can be seen that without adding the halogen-free flame retardant compound, the flame retardant properties of the xenon lamp resistant black halogen-free flame retardant nylon after xenon lamp exposure and aging will be worse; from the comparison between comparative example 2 and embodiment 2, it can be seen that without adding the water and oxygen barrier modifier, the color difference of the xenon lamp resistant black halogen-free flame retardant nylon after xenon lamp exposure and aging will be larger, the hardness will be worse, and the expected effect will not be achieved; from the comparison between comparative example 3 and embodiment 2, it can be seen that when the glass fiber is not immersed, the color difference of the xenon lamp resistant black halogen-free flame retardant nylon after xenon lamp exposure and aging will be larger, the hardness and flame retardant properties will be worse, and the expected effect will not be achieved.

[0067] The present invention can also have many other embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art can make various corresponding changes and modifications based on the present invention, but these corresponding changes and modifications should all fall within the scope of protection of the claims attached to the present invention.

Claims

1. A method for preparing black halogen-free flame-retardant nylon resistant to xenon lamp exposure aging, characterized in that: The raw materials for preparing the xenon lamp exposure aging resistant black halogen-free flame-retardant nylon include the following components based on 100% by weight: 30-50% polyamide resin, 10-30% glass fiber, 10-30% halogen-free flame retardant compound, 1-3% antioxidant, 5-15% water-oxygen barrier modifier, and 1-3% black masterbatch.

2. The method for preparing xenon lamp exposure aging resistant black halogen-free flame retardant nylon according to claim 1, characterized in that: The weight average molecular weight of the polyamide resin is 18 to 25 kDa.

3. The method for preparing xenon lamp exposure aging resistant black halogen-free flame retardant nylon according to claim 1, characterized in that: The halogen-free flame retardant compound is prepared by mixing nano silicon dioxide, zinc borate, magnesium hydroxide and ammonium polyphosphate; the mass ratio of the nano silicon dioxide, zinc borate, magnesium hydroxide and ammonium polyphosphate is 10-20:1:2-5:8-20.

4. The method for preparing xenon lamp exposure aging resistant black halogen-free flame retardant nylon according to claim 1, characterized in that: The water and oxygen barrier modifier is prepared by reacting ethyl oleate, bis(acetylacetonato) diisopropyl titanate and tea polyphenols.

5. The method for preparing xenon lamp exposure aging resistant black halogen-free flame retardant nylon according to claim 1 or 4, characterized in that: The preparation of the water-oxygen barrier modifier comprises the following steps: S1: Add an appropriate amount of toluene into a reaction vessel equipped with a stirrer, a thermometer, and a reflux condenser, and heat to a certain temperature; S2: adding ethyl oleate to the reaction vessel in step S1, stirring to fully dissolve it, and then slowly dropping bis(acetylacetonato)diisopropyl titanate, stirring is maintained during the dropping process, and after the dropping is completed, reacting at a certain temperature for a period of time; S3: After the reaction is completed, tea polyphenols are slowly added to the reaction vessel in step S2 in batches, and the temperature is increased to react for a period of time; S4: After the reaction is completed, the reaction product is cooled to room temperature, and then filtered, distilled, and purified to obtain a water-oxygen barrier modifier.

6. The method for preparing xenon lamp exposure aging resistant black halogen-free flame retardant nylon according to claim 5, characterized in that: The mass ratio of ethyl oleate, bis(acetylacetonato)diisopropyl titanate and tea polyphenol is 5-10:0.5-2:

1.

7. The method for preparing xenon lamp exposure aging resistant black halogen-free flame retardant nylon according to claim 1, characterized in that: The following steps are involved: Step 1: Add polyamide resin, halogen-free flame retardant compound, antioxidant, water-oxygen barrier modifier and black masterbatch into a high-speed mixer for premixing, the speed of the high-speed mixer is 500-1000 rpm, and the mixing time is 5-10 minutes; Step 2: soaking the glass fiber in a silane coupling agent solution with a mass concentration of 1 to 3% for 10 to 30 minutes, taking out the glass fiber after soaking, drying it and setting it aside; Step 3: Add the premixed material in step 1 and the soaked glass fiber in step 2 into a twin-screw extruder for extrusion granulation, the extrusion temperature is 200-260° C., and the screw speed is 100-300 rpm; Step 4: After the material is extruded, it is cooled and vacuum dried to obtain black halogen-free flame-retardant nylon that is resistant to xenon lamp exposure and aging.

8. The method for preparing xenon lamp exposure resistant black halogen-free flame-retardant nylon according to claim 5, characterized in that: The heating temperature of step S1 is 80-100° C.; the stirring speed of step S2 is 100-300 rpm, the reaction temperature is 80-100° C., and the reaction time is 2-4 hours; the reaction temperature of step S3 is 100-120° C., and the reaction time is 4-6 hours.

9. The method for preparing xenon lamp exposure aging resistant black halogen-free flame retardant nylon according to claim 1, characterized in that: The antioxidant is one or more of antioxidant 1098, antioxidant 1010, antioxidant 1216, and antioxidant 1330.

10. Application of the xenon lamp resistant black halogen-free flame-retardant nylon prepared by the method for preparing xenon lamp resistant black halogen-free flame-retardant nylon according to any one of claims 1 to 9 in automobile supporting plastic parts or automobile engine peripheral parts.

Citation Information

Patent Citations

  • Anti-ultraviolet halogen-free flame-retardant nylon composition used for fasteners, and preparation method thereof

    CN108795037A

Cited By

  • Bio-based macromolecular flame retardant, preparation method thereof and flame-retardant nylon material

    CN120271815A